2009
DOI: 10.1088/0031-9155/54/9/001
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive transcranial ultrasound therapy based on a 3D CT scan: protocol validation andin vitroresults

Abstract: A non-invasive protocol for transcranial brain tissue ablation with ultrasound is studied and validated in vitro. The skull induces strong aberrations both in phase and in amplitude, resulting in a severe degradation of the beam shape. Adaptive corrections of the distortions induced by the skull bone are performed using a previous 3D computational tomography scan acquisition (CT) of the skull bone structure. These CT scan data are used as entry parameters in a FDTD (finite differences time domain) simulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
160
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(166 citation statements)
references
References 36 publications
(35 reference statements)
1
160
0
Order By: Relevance
“…[9][10][11][12] In finite difference methods, partial derivatives are calculated using a linear combination of function values at neighboring grid points. The finite difference approximations are derived by combining local Taylor series expansions truncated to a fixed number of terms.…”
Section: Numerical Methods For Ultrasound Propagationmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12] In finite difference methods, partial derivatives are calculated using a linear combination of function values at neighboring grid points. The finite difference approximations are derived by combining local Taylor series expansions truncated to a fixed number of terms.…”
Section: Numerical Methods For Ultrasound Propagationmentioning
confidence: 99%
“…Chauvet et al 11 confirmed the potential for model-driven TR-based focusing inside the human head to millimeter precision, verified by MRI thermometry. Marquet et al 12 showed that model-driven TR is capable of restoring 90% of the peak pressure that can be obtained with gold-standard hydrophone based methods when focusing through an ex vivo skull bone. However, model-driven TR remains subject to systematic errors and uncertainties with a resulting loss in focusing quality or efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorption values are inflated to imitate the effect of scattering & reflective losses in the skull layer, which are the dominant attenuating effects [11]. This technique has been used in multiple studies, including a modification using a homogeneous absorption map [12,13]. Several other models based on empirical relationships between CT derived density and acoustic sound speed and absorption have been also proposed [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in ultrasound transducer technology 3,6,7,27,28,36,37,51,52,60 have enabled transcranial sonication to be precisely focused to deep targets in the brain with MR guidance and temperature monitoring, 8,15,30,40,42 avoiding the superficial burns that were noted in earlier studies. 35 In fact, the first human trials for treatment of glioma and neuropathic pain have proven that FUS can be delivered through the intact human skull to heat targets 39 and even ablate them 38 with precision.…”
mentioning
confidence: 99%